Checklist of Rhopalocera fauna of District Srinagar in Jammu and Kashmir Union Territory, India (Lepidoptera: Papilionoidea) - Huma Nisar (SHILAP)
The survey carried out in March - December 2021 has revealed the presence of Forty-seven Rhopalocera species under the families: Hesperiidae, Lycaenidae, Nymphalidae, Papilionidae and Pieridae, belonging to 37 genera and five families from district Srinagar.